Embedding European values in data governance: A case for public data commons - Jan J. Zygmuntowski; Laura Zoboli; Paul Nemitz (Internet Policy Review, 2021)
The public sphere needs an "ecosystem of trust" which could set out objectives of re-usage of data for the common good while protecting individual rights. This study analyses the emerging models of data governance through the lenses of science and technology studies (STS), critical data studies (CDS), and institutional economics, investigating which data governance model creates conditions for data stewardship guided by European values and rights. We critically examine two prominent, yet highly arguable, paradigms related to data, asserting that the systemic level of data assemblage must be re-conceptualised to reject the data-as-a-commodity view and take public interest into consideration. For data stewardship to achieve its goals, it is necessary to consider the inherent properties of data as commons, in the sense of a common-pool resources (CPR) framework. Therefore, we point towards public data commons as the model that is best suited to secure European rights and values while increasing data sharing at the same time. The design of such public data commons is the challenge of our time.
Keywords: 300; Data governance; Internet policy; Data commons; Public interest; Trust; European values